2014
DOI: 10.1108/imds-10-2013-0429
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership, work engagement, and voice behavior

Abstract: Purpose The purpose of this paper is to draw on ethical leadership and regulatory focus theory perspectives to examine the mediating role of work engagement in the relationship between ethical leadership and voice behavior, and it addresses the moderating effect of promotion focus on the relationship between ethical leadership and work engagement. Design/methodology/approach The paper uses a sample of 239 supervisor subordinate dyads collected from a large economic research institution in northern Taiwan to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 35 publications
2
49
0
3
Order By: Relevance
“…It has a critical influence on the work environment, integrity, values, moral principles, and competence of employees [1,33]. Cheng et al [34] concluded that a leader's ethics influence their behaviors. Research such as that by Avolio and Gardner [35] or Brown and Trevino [36] proposes that an ethical leader's behavior brings a positive outcome to a CEOs' performance.…”
Section: The Concept and Its Implicationsmentioning
confidence: 99%
“…It has a critical influence on the work environment, integrity, values, moral principles, and competence of employees [1,33]. Cheng et al [34] concluded that a leader's ethics influence their behaviors. Research such as that by Avolio and Gardner [35] or Brown and Trevino [36] proposes that an ethical leader's behavior brings a positive outcome to a CEOs' performance.…”
Section: The Concept and Its Implicationsmentioning
confidence: 99%
“…First, this study provides a new perspective for understanding the effect of ethical leadership on their subordinates. While previous studies had linked ethical leadership to work engagement [44,79], we go a step further to explore how ethical leadership affects young teachers' work engagement. This study empirically tests the proposition argued by Brown and Treviño [37] that ethical leadership is related to employees' outcomes.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Kacmar, Carlson, & Harris, 2013), no voice behavior (Cheng, Chang, Kuo, & Cheung, 2014;Walumbwa, & Schaubroeck, 2009;Wang, Gan, Wu, & Wang, 2015) e na safety performance (e.g. Chughtai, 2015).…”
Section: Efeitos Da Liderança éTicamentioning
confidence: 99%